LEGAL PERSPECTIVE ON ASEAN ECONOMIC COMMUNITY - Darminto Hartono; Soekotjo Hardiwinoto (Fakultas Hukum, Universitas Diponegoro, 2018)
Since 2015, the ASEAN Economic Community (AEC) applied in its member countries, Including Indonesia. The preparation effort is regulatory legislation related to the AEC as a guide to achieve country's goals. The research aims to focus on how to inventory of the AEC regulations and how to find out in passing the AEC. The method uses the normative juridical approach and qualitative descriptive data analysis method. These research results that have a global market share, exporting country, investment destination country, a liberalization of ASEAN goods trade, large demographic bonuses, open services sector, aand smoother capital flows constantly. While the challenge is the elevation of the rate of export-import and the inflation rate, the negative impact of broader capital flows, the similarity of export products Which is still diverse must be solved. The Indonesian Government has an authority to regulate the role and function through it policies optimally, because of the opportunities and the existence of Indonesia. It is a matter of course that each member country to face AEC still not enough of expectations.